Hubungan Antara Kekuatan Otot Lengan Dengan Uchikomi Karet Terhadap Bantingan Teknik Tai-Otoshi pada Atlet Judo di Padepokan Judo Kesatria Bhayangkara - Dicky Wahyudi Nasution; Juli Candra; Ahmad Muhlisin Natas Pasaribu; Desy Tya Maya Ningrum; Asrori Yudha Prawira (Jurnal Sosial Teknologi, 2026)
The tai-otoshi slam is an important technique in judo that requires arm muscle strength and technical mastery. The rubber uchikomi method as a repetitive exercise is considered effective in improving technique and increasing muscle strength. This study aimed to analyse the relationship between arm muscle strength, rubber uchikomi method, and tai-otoshi technique ability in judo athletes at Padepokan Judo Kesatria Bhayangkara (PJKB). This study used a descriptive quantitative method with a correlational approach. A total of 66 judo athletes from PJKB were sampled. The independent variables were arm muscle strength and rubber uchikomi method, while the dependent variable was tai-otoshi technique ability. Data were collected through muscle strength tests, training observations, and tai-otoshi technique assessments, then analysed using Pearson's correlation test and multiple linear regression. The study showed a significant relationship between arm muscle strength and tai-otoshi technique ability (r = 0.898, p < 0.01), as well as a positive relationship between the rubber uchikomi method and tai-otoshi technique (r = 0.367, p < 0.01). Simultaneously, arm muscle strength and rubber uchikomi method had a very strong relationship with tai-otoshi technique ability (R = 0.917, R² = 0.841, p < 0.01). This result confirms the importance of combining arm muscle strength training with the rubber uchikomi method to improve tai-otoshi technique mastery. Strength training provides power and stability, while rubber uchikomi improves movement patterns and builds muscle memory. Arm muscle strength and the rubber uchikomi method significantly contributed to the performance of the tai-otoshi technique. Coaches are advised to integrate these two methods in judo athletes' training programmes to improve technique effectiveness.